2015
DOI: 10.4149/gpb_2015004
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of PDE4B polymorphisms with schizophrenia and smooth pursuit eye movement abnormality in a Korean population

Abstract: Abstract. Schizophrenia is a debilitating mental disorder with a high heritability rate. Located on chromosome 1p31.3, the human cAMP-specific 3',5'-cyclic phosphodiesterase 4B (PDE4B) gene has been considered as an important candidate gene for the risk of schizophrenia. Several genetic association studies reported the association between PDE4B polymorphisms and the risk of schizophrenia in Caucasian, African American, Indian, and Japanese populations. The aim of this study is to examine the association of PDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Next, 106 irrelevant citations were excluded through screening of titles and abstracts and 15 articles were assessed for eligibility. After excluding seven citations for being not case-control studies, two studies [ 19 , 23 ] for insufficient data, though we tried to contact the authors for more information, and one study written in Chinese, five case-control studies [ 21 , 22 , 24 26 ] were finally included for this meta-analysis. The excluded articles and reasons were listed in S1 Text .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, 106 irrelevant citations were excluded through screening of titles and abstracts and 15 articles were assessed for eligibility. After excluding seven citations for being not case-control studies, two studies [ 19 , 23 ] for insufficient data, though we tried to contact the authors for more information, and one study written in Chinese, five case-control studies [ 21 , 22 , 24 26 ] were finally included for this meta-analysis. The excluded articles and reasons were listed in S1 Text .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, they identified 14 SNPs of PDE4B gene associated with schizophrenia under a nominal P value of 0.05 [ 18 ]. Indeed, there have been accumulating studies investigating association of PDE4B variations with predisposition to schizophrenia across multi-ethnic populations, including Caucasian populations (Europeans [ 19 21 ], Caucasian Canadians [ 22 ] and Caucasian Americans [ 23 ]), Asian populations (Indians [ 18 ], Japanese [ 24 ], Chinese [ 25 ] and Koreans [ 26 ]), and African populations (African Americans [ 23 ]). The only meta-analysis concerning the association of PDE4B SNPs and schizophrenia was taken in Bae’s study[ 26 ], which just combined Korean population in their own study and Japanese population in Numata’s study[ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rs1040716 substitution, in addition to being associated with PD [23], has also been shown to be associated with schizophrenia [24],[32],[33], however, other studies did not find any associations between rs1040716 and schizophrenia [8],[34]. SNPs rs10454453 and rs502958 have been studied in relation to panic disorder only [23].…”
Section: Resultsmentioning
confidence: 99%
“…The phosphodiesterase 4B (PDE4B) gene is located in chromosome 1P31, which is a region of susceptibility genes linked to psychiatric disorders . Cell lines derived from family members with the t (1;16) translocation revealed that PDE4B protein expression was reduced by 50% .…”
Section: Introductionmentioning
confidence: 99%